2018
DOI: 10.1111/bjh.15530
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary arterial hypertension – a unrecognized cause of high‐shear high‐flow haemostatic defects (otherwise referred to as acquired von Willebrand syndrome) in children

Abstract: Acquired von Willebrand syndrome (AVWS) is reported in high-flow high-shear congenital cardiac disorders. We hypothesized that the narrowed pulmonary vasculature in idiopathic pulmonary arterial hypertension (IPAH) may induce AVWS. We conducted a cross-sectional evaluation of children with IPAH. Patients with bleeding symptoms and/or laboratory abnormalities (thrombocytopenia, anomalies in coagulation screening tests) were tested in-depth for haemostatic defects. Fourteen children were followed with IPAH of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
16
2
Order By: Relevance
“…Lastly, we evaluated VWF:Ag and VWF:Acin our study population, which were found to be decreased in PAH patients compared to controls, along with the VWF Ac/Ag ratio. Some studies in the field have linked PAH with acquired von Willebrand syndrome [ 27 , 28 ]. VWF multimers are particularly large in size, making them vulnerable to biophysical forces, including shear stress [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we evaluated VWF:Ag and VWF:Acin our study population, which were found to be decreased in PAH patients compared to controls, along with the VWF Ac/Ag ratio. Some studies in the field have linked PAH with acquired von Willebrand syndrome [ 27 , 28 ]. VWF multimers are particularly large in size, making them vulnerable to biophysical forces, including shear stress [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…PAH is a chronic and progressive disorder, where endothelial dysfunction plays a central role in its development and evolution [ 27 ]. The chronic injury to the pulmonary endothelium could result in chronic platelet and coagulation cascade activation, extended platelet degranulation and, subsequently, in platelet function abnormalities [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 52 Subsequent studies have shown low and low–normal levels of vWF antigen and activity in PAH. 53 , 54 These results were attributed to an acquired von Willebrand syndrome in the context of a ‘high-shear high-flow’ circulation.…”
Section: Platelets In Pahmentioning
confidence: 99%
“…Anticoagulation with warfarin or phenprocoumon was once not recommended on a routine basis in children with idiopathic pulmonary arterial hypertension (6). Chronic anticoagulation can be useful in patients with progressive IPAH/HPAH (empirical goal INR 2.0 to 2.5), patients with CTEPH, patients with low cardiac output, and those with hypercoagulable states (7).…”
Section: Conventional and Supportive Therapymentioning
confidence: 99%
“…must be weighed against potential benefits in patients with low cardiac output. Often right heart failure will be associated with bleeding symptoms and/or anomalies in coagulation screening tests (6).…”
Section: Conventional and Supportive Therapymentioning
confidence: 99%